Aktivitas Antibakteri Ekstrak Karang Lunak Sarcophyton sp. yang Difragmentasi dan Tidak Difragmentasi dari Perairan Pulau Pramuka, Kepulauan Seribu, Jakarta - Kawaroe, Mujizat; Soedarma, Dedi; Effendi, Hefni; Nurhayati, Tati; Hardiningtyas, Safrina Dyah (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Fragmented and non-fragmented soft corals showed antibacterial activities. Soft corals were gradually extracted using methanol, ethyl acetate, and hexane. Crude extract of the samples was tested its antibacterial activity, Minimun Inhibitory Concentration, toxicity (Brine Shrimp Lethality Test method), and phytochemicals. Overall, the antibacterial activity of crude extract of non-fragmented soft coral Sarcophyton sp. was higher than the crude extract of fragmented soft coral Sarcophyton sp. Crude ethyl acetate extract showed higher antibacterial activities. The ethyl acetate crude extract of non-fragmented soft coral Sarcophyton sp. is able to inhibit all tested bacteria is E. coli, S. aureus, P. aeruginosa and B.cereus, while the ethyl acetate crude extract of fragmented Sarcophyton sp. is unable to inhibit bacteria P. aeruginosa. Minimum inhibitory concentration extracts of non-fragmented Sarcophyton sp. in range 240âˆ’480 Î¼g/disc. The 24-h LC50 extracts of fragmented and non-fragmented Sarcophyton sp. for Artemia salina were 149.50 ppm and 45.15 ppm, respectively. Bioactive compounds of fragmented and non-fragmented Sarcophyton sp. extract are steroid, flavonoid and alkaloid.